Development and validation of estimates of Glomerular Filtration Rate (GFR) equations in the Malaysian setting - Md Ralib, Azrina; Mohd Hanafiah, Farah Nadia; Ab. Rashid, Iqbalmunauwir; Dzaharudin, Fatimah; Abd Rahim, Mohamad Shahrir (2021)
Introduction: Accurate assessment of glomerular filtration rate (GFR) in perioperative and intensive care patients is very important for diagnostic and therapeutic intervention. Clinically, GFR is estimated from plasma creatinine using equations such as Cockcroft-Gault, Modification of Diet in Renal Disease, and Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) equations. However, these were developed in the Western population. There was no equation that has been developed specifically in our population. Objectives: We developed a new equation based on the gold standard of 99mTc-DTPA imaging measured GFR. We then performed an internal validation by comparing the bias, precision and accuracy of the new equation, and the other equations with the gold standard of 99mTc-DTPA imaging measured GFR. Methods: This was a cross sectional study using the existing record of patients that was referred for 99mTc-DTPA imaging at the Nuclear Medicine Centre, International Islamic University Malaysia. As this is a retrospective study utilizing routinely collected data from the existing pool of data ethical committee has waived the need for informed consent. Results: Data of 187 patients was analysed from January 2016 to March 2021. Of these, 94 were randomized to the development cohort, and 93 to the validation cohort. A new equation of eGFR was determined as 16.637 * 0.9935Age * (SCr/23.473)-0.45159. In the validation cohort, both CKD-EPI and the new equation had the highest correlation to 99mTc-DTPA with correlation coefficient of 0.81 (p<0.0001). However, the new equation had the least bias and was the most precise (mean bias of -3.58 ± 12.01) and accurate (P30 of 64.5% and P50 of 84.9%) compared to the other equations. Conclusion: The new equation which was developed specifically using our local data population was the most accurate and precise, with less bias compared to the other equations. Further study validating this equation in the perioperative and intensive care patients is needed.